135k views
4 votes
6^2+(3⋅4)−2^4 does any one get this

User Benroth
by
4.7k points

1 Answer

2 votes

Answer:

Explanation:

This seems you are going to evaluate the expression using Order of Operations.

Use PEMDAS and solve in order

P - parenthese

E - exponents

MD - multiply and divide (left to right, whichever comes first)

AS - add and subtract (left to right, whichever comes first)


6^(2) + (3*4) - 2^(4)

Evaluate what is inside the parenthesis first


6^(2) + 12 - 2^(4)

Next, evaluate the exponents.


6^(2) = 6* 6 = 362^(4) = 2*2*2*2 = 4*2*2 = 8*2 = 16\\36 + 12 - 16

Add and subtract going left to right.


36 + 12 - 16\\48 - 16\\32

The answer is 32 when you evaluate the expression.

User Ossan
by
4.5k points